2008
DOI: 10.1016/j.juro.2008.01.095
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Extracorporeal Shock Wave Lithotripsy on Renal Function: Our Experience With 156 Patients With Solitary Kidney

Abstract: The demonstrated effectiveness, small number of complications at short-term followup, insignificant effect on renal function, blood pressure and relatively small number of recurrences at the long-term followup confirm that shock wave lithotripsy is not only effective but is also safe in the long run.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Not only do urologic procedures manage the kidney stone event itself, our study provides evidence that they may help to prevent long-term deterioration in kidney function as seen in previous studies. 6,[12][13][14][15][16][17] Limitations There were several limitations to this study. Patients with kidney stones were identified either by seeking medical care for symptoms related to an acute episode or incidentally on imaging such as computed tomography or ultrasound.…”
Section: Hazards Among Stone Formers After Urologic Proceduresmentioning
confidence: 98%
See 1 more Smart Citation
“…Not only do urologic procedures manage the kidney stone event itself, our study provides evidence that they may help to prevent long-term deterioration in kidney function as seen in previous studies. 6,[12][13][14][15][16][17] Limitations There were several limitations to this study. Patients with kidney stones were identified either by seeking medical care for symptoms related to an acute episode or incidentally on imaging such as computed tomography or ultrasound.…”
Section: Hazards Among Stone Formers After Urologic Proceduresmentioning
confidence: 98%
“…Female gender and an immediate postoperative improvement in the modification of diet in renal disease eGFR are predictive of a sustained increase in that rate of renal preservation. 16 El-Asemy et al 17 did not find any significant effect on renal function or blood pressure at the one-year follow-up after ESWL in patients with a solitary kidney. Percutaneous nephrolithotomy, ESWL, or the two techniques combined were found to be equally efficacious for preserving renal function in patients with solitary kidney.…”
mentioning
confidence: 91%
“…39 The association between ESWL and the development of chronic diseases (hypertension and diabetes) is unclear and studies with higher levels of evidence are needed to confirm or rule out this association (Level of evidence 2b; Grade of recommendation B). Lastly, in relation to a possible worsening of renal function after ESWL, in a study of 156 patients with a single kidney undergoing ESWL and an average follow up of 3.8 years, El-Assmy et al 40 found no changes in creatinine levels, demonstrating the safety of this method at least in the medium term (Level of evidence: 3; Grade of recommendation B).…”
Section: Complicationsmentioning
confidence: 99%
“…Modern urologic techniques for stone removal, such as extracorporeal shock-wave lithotripsy or percutaneous nephrolithotomy, although generally safe, have some potential risk for renal damage [15]. Whether that risk is increased in patients with a single kidney is still unsettled [16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%